Preliminary Study: Profile of Management of Practicum Activities Science at Middle School Level To Improve Higher Level Thinking Skills, Science Process Skills, and Scientific Attitudes - Bakhtiar Ardiansyah; Agus Ramdani; Aliefman Hakim; Muh Makhrus; M. Yustiqvar (Postgraduate, University of Mataram, 2023)
This study aims to conduct a preliminary study related to the management of science practicum activities at the junior high school level throughout Mataram City. This preliminary study is to obtain an overview of the management of science practicum activities which includes practicum activity planning, implementation of practicum activities and practicum activity assessment. This study uses a qualitative approach with a case study type of research. The research sample consisted of science teachers and students of grades VIII and IX in 3 schools outside the urban areas of Mataram City. The sampling technique uses perposive sampling. Data collection methods used are observation, documentation and questionnaires and interviews. The results showed that the management profile of science practicum activities carried out in order to improve higher-order thinking skills, science process skills and scientific attitudes had reached 69.21 or in the Enough category. For science practicum planning it has reached 54.58 or in the less category. For the implementation of science practicums it has reached 73.43 or in the good category and for the assessment of science practicum activities it has reached 79.38 or in the good category. The results of this study recommend that science teachers apply various models of more effective science practicum implementation in order to achieve science learning outcomes through science practicum activities